Can Educational Games Based Scientific Edutainment Prevent Bullying in Elementary School? - Ika Susianti; Unik Ambar Wati (Universitas Pendidikan Ganesha, 2025)
Bullying is a serious issue that affects the well being of elementary school students, particularly in emotional, social, and academic aspects, thus requiring innovative and integrated preventive approaches within learning practices. This study aims to analyze and examine the effectiveness of scientific edutainment based educational games in bullying prevention through a systematic literature review. The research employed a descriptive qualitative approach using the Systematic Literature Review (SLR) method guided by the PSALSAR framework. Data were collected from scientific articles published between 2020 and 2025 and selected based on predetermined inclusion and exclusion criteria. Data analysis was conducted using thematic analysis to identify patterns, implementation strategies, and learning outcomes related to game design and its impact on strengthening students’ socio emotional skills. The findings indicate that scientific edutainment-based games that integrate social simulations, reflective narratives, and interactive elements enhance students’ empathy, social literacy, communication skills, and conflict resolution abilities. The implications of this study suggest that scientific edutainment can be integrated into learning practices and character education as a systematic, experience based preventive model. This approach has the potential to serve as an effective strategy in supporting bullying prevention through meaningful and value based learning experiences.